Assessing the acetylcholinesterase inhibitory potential of novel pharmacophores for potential treatment of Alzheimer’s disease - Steenkamp, Vanessa (University of Pretoria, 2024)
Thesis (PhD (Pharmacology))--University of Pretoria, 2023.